Pengenalan Teknik Vertikultur dengan Media Batang Pisang sebagai Alternatif Teknik Budidaya Tanaman - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Purna Kusumayana (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
Problems faced by farmers is the lack of or reduced income their farm at the time of wetland swampy submerged in water for over 6 months due to climatic factors, lack of knowledge of farmers about alternative farming can be done in the yard to increase revenue during the waiting paddy can be cultivated, and lack of knowledge about the use of banana stems in the cultivation of plants. The purpose of this activity is to increase the skills farmers who are members of the Ingin Maju II Farmers Group Desa Pasar Senin dan Sukamaju IV Farmers Group Desa Kandang Halang, Amuntai Tengah District of North Hulu Sungai Utara Regency. This public service using direct extension methods that combine lecture and demonstration plots. While the result is the knowledge and skills of farmers to grow with the establishment of 10 demplot verticulture each farmer group.Keywords: Vertikultur, banana stalks, yard, farmer groups.